A Review of Superbug: A Global Threat in Health Care System (Bangladesh Journal of Infectious Diseases, 2018)
The rapid spread and dissemination of the multidrug-resistant bacteria worldwide represents a major public health problem. The development of antibiotics decreased the mortality among the human and animals leading to a better life expectancy. But the injudicious use of antimicrobials and selection pressure the microbes have developed resistance which became more prominent during last few decades. With the evolution of Methicilin-resistant Staphylococcus aureus (MRSA), Hospital-acquired MRSA, Communityacquired MRSA and MDR TB (Multidrug resistant tuberculosis) challenge for the clinicians have increased to a greater extent. The global emergence and dissemination of acquired carbapenemases among gram negative bacteria are considered a major public health problem. Gram-negative bacteria, most notably Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii, are among the most important causes of serious hospital-acquired and community-onset bacterial infections in humans, and resistance to antimicrobial agents in these bacteria has become an increasingly relevant problem. Recent development in nanotechnology based drug delivery system may prove to be solution for combating these resistant bacteria. However policies and regulations for antibiotic use should be formulated to control the further development of resistance among the microbes.Bangladesh Journal of Infectious Diseases 2017;4(1):25-28